2020
DOI: 10.1186/s13049-020-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rewarming methods in unplanned out-of-hospital births from a prospective cohort

Abstract: Background: Mobile intensive care units frequently manage unplanned out-of-hospital births (UOHB). Rewarming methods during pre-hospital management of UOHB have not yet been compared. The aim was to compare rewarming methods used during pre-hospital management in a large prospective cohort of UOHB in France. Methods: We analysed UOHB from the prospective AIE cohort from 25 prehospital emergency medical services in France. The primary outcome was the change in body temperature from arrival at scene to arrival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…These findings are in line with those of a study in Finland, which found hospital diagnosis of neonatal hypothermia to be recorded in 53% of babies born out of hospital, compared with only 0.7% of babies born in hospital. 4 Our findings also concur with research from France, which found that 56% of babies born outside of hospital were hypothermic on arrival at hospital, 16 and that neonatal hypothermia was associated with increased rates of NICU admission. 5 Although our findings suggest better rates of neonatal normothermia following BBA than literature from other areas, 35% remains a significant proportion of babies arriving at hospital hypothermic.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are in line with those of a study in Finland, which found hospital diagnosis of neonatal hypothermia to be recorded in 53% of babies born out of hospital, compared with only 0.7% of babies born in hospital. 4 Our findings also concur with research from France, which found that 56% of babies born outside of hospital were hypothermic on arrival at hospital, 16 and that neonatal hypothermia was associated with increased rates of NICU admission. 5 Although our findings suggest better rates of neonatal normothermia following BBA than literature from other areas, 35% remains a significant proportion of babies arriving at hospital hypothermic.…”
Section: Discussionsupporting
confidence: 87%
“…In these instances, the newborn is more likely to be hypothermic on arrival at hospital, potentially due to ineffective warming by non-professionals. 16 Therefore, the earlier that effective warming measures can be initiated (eg, at the point of calls to EMS), the better the chances of improved outcomes following BBA. A recent Healthcare Safety Investigation Branch (HSIB) report 17 highlighted the fact that UK investigations into poor patient outcomes following BBA do not routinely consider the clinical impact of advice given by EMS call-handlers or recommended work with relevant stakeholders to develop guidance for maternity emergencies during these calls.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects research from both the North East of England11 and other countries,13 which reported similarly low rates of neonatal temperature measurement by emergency medical services (EMS) providers following BBA. This is concerning, as rates of neonatal hypothermia following BBA have been shown to range from 30% to 100%, resulting in increased neonatal intensive care unit admission rates and higher mortality for these newborns 9…”
Section: Discussionmentioning
confidence: 99%
“…For every minute that a newborn is exposed, their temperature can drop by 0.1°C–0.3°C 8. In the UK, paramedics are the clinicians best placed to improve temperature management for BBA newborns; for example, by providing hats, encouraging skin-to-skin contact with the mother, increasing the ambient temperature and/or conveying newborns to hospital when required 9. The risk of neonatal hypothermia following BBA is recognised by the Joint Royal Colleges Ambulance Liaison Committee (JRCALC) guidance on ‘Care of the newborn’, which states that temperature assessment should be one of the ‘initial clinical assessments’ following BBA 10.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested to read the article in the journal by Javaudin et al [1] looking at the re-warming of infants born out-of-hospital. Whilst the authors are to be congratulated for a careful comparison of several different techniques, their conclusions should be interpreted with caution.…”
Section: Sirmentioning
confidence: 99%